Effects of pulmonary rehabilitation on exacerbation number and severity in people with COPD: An historical cohort study using electronic health records - Moore,E; Newson,R; Joshi,M; Palmer,T; Rothnie,K; Singh,S; Majeed,A; Soljak,M; Quint,JK (Chest, 2017)
BackgroundIn previous systematic reviews, predominantly of randomised controlled trials, pulmonary rehabilitation (PR) has been shown to reduce hospital admissions for acute exacerbations of COPD (AECOPD). However, findings have been less consistent for cohort studies. We aimed to compare rates of hospitalized and general practice (GP) treated AECOPD before and after PR.MethodsUsing anonymised data from the Clinical Practice Research Datalink and Hospital Episode Statistics, hospital admissions and GP visits for AECOPD were compared one year before and after PR in patients referred for PR. Exacerbation rates were also compared between individuals eligible and referred for PR with those eligible and not referred.Results69,089 (64%) of the COPD patients in the cohort were eligible for PR. Of these, only 6,436 (9.3%) were recorded as having been referred for rehabilitation. 62, 019 (89.8%) were not referred and 634 (0.98%) declined referral. When combining GP and hospital exacerbations, people who were eligible and were referred for PR had a slightly higher but not statistically significant exacerbation rate (2.83 exacerbations/patient-year 95% CI: 2.66, 3.00) than those who were eligible but not referred (2.17 exacerbations/patient-year 95% CI: 2.11, 2.24).ConclusionsThis study found that less than 10% of patients who were eligible for PR were actually referred. Patients who were eligible and referred for (but not necessarily completed) PR did not have fewer GP visits and hospitalizations for AECOPD in the year after PR compared to those not referred or compared to the year before PR.